The management of childhood sexual abuse by midwifery, nursing and medical providers in Tanzania. (November 2021) - Mkonyi, Ever; Mwakawanga, Dorkasi L.; Rosser, B.R. Simon; Bonilla, Zobeida E.; Lukumay, Gift Gadiel; Mohammed, Inari; Mushy, Stella E.; Mgopa, Lucy R.; Ross, Michael W.; Massae, Agnes F.; Trent, Maria; Wadley, James
Abstract: Background: Child sexual abuse (CSA) is a significant public health problem affecting one billion children aged 2 to 17 globally. The prevalence of CSA in Tanzania is one of the highest; however, how health care providers manage CSA cases has not been studied. Objectives: This study investigated how medical, nursing, and midwifery professionals in Tanzania handle cases of CSA and identified the factors that facilitate or impede the provision of quality care to CSA victims. Methods: Participants were 60 experienced healthcare professionals and 61 health students working in Dar es Salaam, Tanzania. We conducted 18 focus groups stratified by profession (midwifery, nursing, or medicine) and experience (practitioners versus students). Results: Three main themes emerged. First, child abuse management involved using a multi-disciplinary approach, including proper history taking, physical assessment, treatment, and referral. Second, factors that enhanced disclosure of CSA included building rapport, privacy, and confidentiality. Third, factors that impeded care included fear of harm to the child if the abuse was reported, abuse reporting being perceived as a "waste of time" for providers, loss of evidence from the victim, family resistance, poverty, corruption and cultural dynamics. Conclusions: Midwives, nurses and doctors were all experienced in and reported similar challenges in addressing CSA. At a structural level, the ratio of providers to patients in health facilities inhibits quality care. These findings have implications for strengthening CSA policy/guidelines and clinical practice in Tanzania. Mandated CSA training is necessary for midwifery, nursing, and medical students as well as in continuing education courses for more experienced providers. Highlights: Proper management of CSA helps to reveal sexual victims and provide quality care. Privacy, confidentiality, and time allocation facilitate the disclosure of CSA Life-threatening and heavy punishment hinders the disclosure of CSA among children.